2014
DOI: 10.4081/pmc.2014.5
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviruses and breast milk

Abstract: Breast milk has always been the best source of nourishment for newborns. However, breast milk can carry a risk of infection, as it can be contaminated with bacterial or viral pathogens. This paper reviews the risk of acquisition of varicella-zoster virus (VZV) and cytomegalovirus (CMV), herpesviruses frequently detected in breastfeeding mothers, via breast milk, focusing on the clinical consequences of this transmission and the possible strategies for preventing it. Maternal VZV infections are conditions durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
1
0
3
Order By: Relevance
“…Another study by Zarei et al (2013) about the effectiveness of storytelling on physiological anxiety, worry, and social anxiety in hospitalized school-age children suggests that storytelling could reduce all sub-scales of anxiety (RCMAS). These authors introduced storytelling as an effective, inexpensive method and the child’s favorite non-pharmaceutical intervention.20 Tabrizi et al (2015) also evaluated the effect of preoperational education on reducing anxiety among children aged 8–10 years and showed that storytelling for children significantly reduced separation anxiety during anesthesia.21 Rice et al (2008) showed that educational programs that aimed at preoperative anxiety among children reduced their anxiety during hospitalization and caused stable vital signs.22 Messina et al (2014) tried to reduce children’s anxiety before surgery by using clown therapy for distraction and significantly decreased anxiety among children who entered the operating room with the clown.23…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Zarei et al (2013) about the effectiveness of storytelling on physiological anxiety, worry, and social anxiety in hospitalized school-age children suggests that storytelling could reduce all sub-scales of anxiety (RCMAS). These authors introduced storytelling as an effective, inexpensive method and the child’s favorite non-pharmaceutical intervention.20 Tabrizi et al (2015) also evaluated the effect of preoperational education on reducing anxiety among children aged 8–10 years and showed that storytelling for children significantly reduced separation anxiety during anesthesia.21 Rice et al (2008) showed that educational programs that aimed at preoperative anxiety among children reduced their anxiety during hospitalization and caused stable vital signs.22 Messina et al (2014) tried to reduce children’s anxiety before surgery by using clown therapy for distraction and significantly decreased anxiety among children who entered the operating room with the clown.23…”
Section: Discussionmentioning
confidence: 99%
“…Für die Therapie stehen antivirale Medikamente zur Verfügung, deren Einsatz gezielt auf die jeweilige Situation angepasst erfolgt und bei der Frage der Behandlung der maternalen Infektion einer Einzelfallentscheidung und Aufklärung über einen eventuellen Off-Label-Use bedarf [4]. Eine Übertragung des Virus durch Muttermilch findet nicht statt [46], folglich ist betroffenen Müttern das Stillen ihres Kindes gestattet, vorausgesetzt die Brust ist frei von frischen Effloreszenzen ist, und alle anderen Läsionen/Bläschen sind zwingend abgedeckt [43]. Selbstverständlich ist das Berühren der Bläschen zu vermeiden und die Händehygiene konsequent vor jedem Kontakt zum Kind obligatorisch.…”
Section: Herpes-simplex-virus (Hsv)unclassified
“…angepasst erfolgt und bei der Frage der Behandlung der maternalen Infektion einer Einzelfallentscheidung und Aufklärung über einen eventuellen Off-Label-Use bedarf[4]. Eine Übertragung des Virus durch Muttermilch findet nicht statt[46], folglich ist betroffenen Müttern das Stillen ihres Kindes gestattet, vorausgesetzt die Brust ist frei von Hingegen stellt jede Person mit einem floriden Herpes Zoster ein Infektionsrisiko für alle nichtimmunisierten Personen, vor allem seronegative Schwangere dar. Daher ist die Impfung von Frauen im gebärfähigen Alter vor Eintritt der Schwangerschaft die wichtigste Präventionsmaßnah-me.…”
unclassified